The role of psychological factors in pain modulation - Ivanec, Dragutin (Array, 2010)
„Never again, after 1965, could anyone try to explain pain exclusively in term of peripheral factors“. Namely, this year Melzack and Wall have published their gate control theory. The gate control theory's most important contribution to understanding pain was its emphasis on central neural mechanism in pain modulation. In every sensation system, central representation of impulses from periphery can be significantly modified by numerous contextual factors. However, in the case of pain, it is evidently more emphasised. Central nervous system processes can significantly change expected outcomes, regarding the intensity and pain quality. For example (pathological cases excluded) there is no evidence that a person perceived red colour as blue just because he/she had taken a „magic potion“. However, it has been proven that taking of an „inactive pill“ (placebo) can significantly reduce pain sensation. Attention, expectation, learning, stress and conditions of changed consciousness are some of psychological factors that have been known to have an effect on modulation of pain intensity. Modern studies are focused on biological processes and mechanisms that could explain relatively large potential effect of mentioned psychological processes in central nervous system on pain modulation. The most important question for further research is to understand complex interaction of factors which contribute in pain perception, including psychological ones.